Diagnosis and management of cardiovascular risk in nonalcoholic fatty liver disease. (July 2015) - Lonardo, Amedeo; Ballestri, Stefano; Targher, Giovanni; Loria, Paola
<x xml:space="preserve">Abstract</x> Nonalcoholic fatty liver disease (NAFLD) is increasingly recognized as an important cardiovascular risk (CVR) factor. This is a narrative clinical review aimed at answering how diagnosis and management of CVR should be conducted in the individual patient with NAFLD. To this end, the authors performed an extensive search of the existing literature on PubMed (1993–2014) using pertinent keywords. To date, CVR among patients with NAFLD might be assessed with the Framingham risk score equation or other risk calculators, to be adapted to the true CVR in the specific population being assessed; however, the use of these CVR calculators needs to be validated by future studies in larger cohorts of NAFLD patients of various ethnic backgrounds in order to substantiate their clinical relevance as a foundation for the primary prevention of cardiovascular diseases in this group of patients. Early and aggressive drug treatment of CVR should be started in NAFLD patients with a history of cardiovascular events, established diabetes or who are at high (calculated) CVR. Whether such an aggressive pharmacological approach is also justified in patients with NAFLD, who are at intermediate or low CVR, remains debatable. Currently, there are no clinical trials showing that the treatment of NAFLD per se (either associated or unassociated with traditional CVR factors) will result in decreased risk of cardiovascular events. Accordingly, drug treatment should be better individualized, aiming at correcting all the coexisting cardio-metabolic risk factors of the individual patient with NAFLD. To this end, an overview of the lifestyle interventions and the available drugs is offered, emphasis being conveyed to statins and metformin, which promise to cover worrying complications of NAFLD such as the risk of developing hepatocellular carcinoma.